2019
DOI: 10.1371/journal.pone.0226108
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of A(H5N1) clade 2.3.2.1c avian influenza viruses with evidence of reassortment in Cambodia, 2014-2016

Abstract: In Cambodia, highly pathogenic avian influenza A(H5N1) subtype viruses circulate endemically causing poultry outbreaks and zoonotic human cases. To investigate the genomic diversity and development of endemicity of the predominantly circulating clade 2.3.2.1c A(H5N1) viruses, we characterised 68 AIVs detected in poultry, the environment and from a single human A(H5N1) case from January 2014 to December 2016. Full genomes were generated for 42 A(H5N1) viruses. Phylogenetic analysis shows that five clade 2.3.2.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…Sequence analysis of the hemagglutinin (HA) and neuraminidase (NA) genes of several A/H5N1 isolates using Sanger methodology revealed the influenza A/H5N1 viruses to be typical of other clade 2.3.2.1c viruses circulating in LBMs during 2015–2016 (Suttie et al, 2019 ). Comparison of HA and NA sequences from air and poultry samples shows direct correlation, indicating that poultry within the LBM were the source of the viruses in the air (Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sequence analysis of the hemagglutinin (HA) and neuraminidase (NA) genes of several A/H5N1 isolates using Sanger methodology revealed the influenza A/H5N1 viruses to be typical of other clade 2.3.2.1c viruses circulating in LBMs during 2015–2016 (Suttie et al, 2019 ). Comparison of HA and NA sequences from air and poultry samples shows direct correlation, indicating that poultry within the LBM were the source of the viruses in the air (Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we reported the reassortant H5N1 virus infection in a Thai patient. Nevertheless, the reassortant H5N1 virus infection in humans had been previously reported in Vietnam [34,35] and Cambodia [36].…”
Section: Discussionmentioning
confidence: 97%
“…The full genomes of the clade 1 viruses (W0526301 and X0817302) included in this study have been previously published [10]. The genome of the clade 2.3.2.1c virus has also been previously published [15]. The accession numbers and other relevant information for all three viruses are included in Supplementary Table 1.…”
Section: Viral Strainsmentioning
confidence: 99%